ಆಧುನಿಕ ಕೊಂಕಣಿ ಕತೆಗಳು - (:unkn) unknown (Konkani Language and Cultural Foundation, Mangaluru, 2013)
This book is a translation of Konkani Short Stories
Adhunika Konkani Kathegalu
Keywords: Konkani; Short Stories; Konkani; Konkani